Neurobiological Approaches on Brains of Children with Dyslexia: Review - Caylak, Emrah (Elsevier Science Inc, 2009)
Learning difficulties commonly comprise a heterogeneous group of disorders manifested by unexpected problems in some children's experiences in the academic performance arena. These problems especially comprise of a variety of disorders, which one of the most well-recognized learning difficulties is reading disability or dyslexia. The aim of this review is to explain the postmortem, structural or functional neuroimaging, and electrophysiological studies of human brains in children. The findings about these neuropathological and neurofunctional characteristics of developmental dyslexia, prospective studies beginning early in the life span and studies targeting remedial intervention will help to set the research agendas for future studies to follow.
Keywords: Dyslexia; magnetic resonance imaging (MRI); diffusion tensor imaging (DTI); functional MRI (fMRI); electrophysiological